Effects of Flow Rate on Delivery of Bubble Continuous Positive Airway Pressure in an In Vitro Model - Tsyr-Yuh Ho; Shan-Fu Ou; Shih-Hui Huang; Chi-Ning Lee; Luo-Ping Ger; Kai-Sheng Hsieh; Hui-Ying Cheng; Wei Yang Lee; Ken-Pen Weng (Elsevier, 2010)
There has been concern over the effect of vigorous bubbling on the delivery pressure during the operation of the bubble nasal continuous positive airway pressure (CPAP) system. We investigated the relationship between intra-tubing pressure changes and flow rates in a closed bubble CPAP system in vitro. Methods: Using an experimental (in vitro) model, the distal connecting tube of the CPAP system was immersed under the water seal to a depth of 5 cm. Sixteen different flow rates, ranging from 2 L/min to 20 L/min, were tested. The procedure was repeated 10 times at each flow rate, and the intra-tubing pressure was recorded. Results: The intra-tubing pressure within the model increased as the air flow rates were adjusted from 2 L/min to 20 L/min. The relationship was represented by the following equation, pressure (cmH2O) = 5.37 + 0.15 × flow rate (L/min) (R2 = 0.826, p < 0.001). Conclusion: These results demonstrated that the intra-tubing pressure in a bubble CPAP system was highly correlated with flow rate in vitro.